2018
DOI: 10.5614/j.eng.technol.sci.2018.50.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Parameter Optimization of a Linear Vibrating Banana Screen Using DEM 3D Simulation

Abstract: In this paper, the effects of vibration parameters of a banana screen, i.e. frequency, amplitude and vibration direction angle, on the screening efficiency per unit time were studied using the discrete element method (DEM). The simulations were validated according to data collected from an experimental prototype screen. Functional relationships between vibration parameters and screening efficiency per unit time are presented. The results showed that the screening efficiency per unit time first displays an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Failure diagnosis requires accurate dynamic modeling and system identification [6]. In recent years, many studies have reported on the dynamic modeling [7][8][9][10], dynamic design [11][12][13][14], dynamic optimization [15][16][17][18][19][20], particle motion analysis [21][22][23][24], and spring failure diagnosis of vibrating screens [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Failure diagnosis requires accurate dynamic modeling and system identification [6]. In recent years, many studies have reported on the dynamic modeling [7][8][9][10], dynamic design [11][12][13][14], dynamic optimization [15][16][17][18][19][20], particle motion analysis [21][22][23][24], and spring failure diagnosis of vibrating screens [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 DEM has been widely used in many scientific and technological fields such as mineral processing, chemical engineering, applied physics, and agricultural engineering. [14][15][16][17][18][19][20] There are many studies on the screening process based on DEM simulation. Weerasekara and Deen et al used two-dimensional DEM to simulate the movement of small particles through the screen during the screening process.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 DEM has been widely used in many scientific and technological fields such as mineral processing, chemical engineering, applied physics, and agricultural engineering. 1420…”
Section: Introductionmentioning
confidence: 99%
“…Being aware of the travelling mode of solid particle on flat surface is the key element helping to optimize the mechanical separation process of a heterogeneous mix of solid particles [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of a solid particle on a flat oscillating surface, due to its complexity, is studied theoretically, by using different types of software to achieve the simulation of this process [9][10][11][12] or using different mathematical methods [4,13,14], as well as practically, by making experimental determinations for different working conditions or for different facilities [12][13][14].…”
Section: Introductionmentioning
confidence: 99%